Innocence road [large type] - Griffin, Laura, 1973- (Center Point Large Print, 2026)
"Leanne Everhart knows women have something to fear in her artsy hometown, especially so if they're not rich, white locals. Returning to town after her father's death, she sees the ugliest sides of an area that draws people for its severe, untamed natural landscape. While her department faces mounting backlash over a recent wrongful conviction in the long-ago murder case of a popular local teenager--which is now unsolved--Leanne is called to a fresh crime scene at the edge of the desert. A nameless woman was found murdered, with no clues as to her identity. As Leanne digs into the crime scene evidence, she grows convinced this latest murder case is linked with the local teenager's murder. And to multiple cold cases, all unnamed female victims, that have all been shelved by her department without leads. Now, with conflicted loyalties and without allies, Leanne must hunt down a serial killer, one who's been preying on local women for two decades, growing bolder and more ruthless with every strike."--